Modeling of a new semi-active/passive magnetorheological elastomer isolator - Behrooz, Majid; Wang, Xiaojie; Gordaninejad, Faramarz (Smart materials and structures, 2014)
This paper presents theoretical modeling of a new magnetorheological elastomer (MRE) base isolator and its performance for vibration control. The elastomeric element of the traditional steel-rubber base isolator is modified to a composite layer of passive elastomer and MRE which makes the isolator controllable with respect to its stiffness and damping. The proposed variable stiffness and damping isolator (VSDI) is designed based on an optimized magnetic field passing through MRE layers to achieve maximum changes in mechanical properties. The controllability of the VSDI is investigated experimentally under double lap shear tests. A model employing the Bouc-Wen hysteresis element is proposed to characterize the force-displacement relationship of the VSDI. An integrated system which consists of four VSDIs is designed, built and tested. Dynamic testing on the integrated system is performed to investigate the effectiveness of the VSDIs for vibration control. Experimental results show significant shift in natural frequency, when VSDIs are activated and the possibility of using the VSDIs as a controllable base isolator.